Analysis of expression and transport activity of sugar transporter gene HpSWEET7 from red pitaya - ZHENG Qianming; YAN Shuang; XIE Pu; WANG Honglin; MA Yuhua (Xibei zhiwu xuebao)
[Objective] The red pitaya (Hylocereus polyrhizus) HpSWEET7 gene, belonging to the sugar transporter SWEET (sugars will eventually be exported transporter) family, was cloned and its role in fruit sugar accumulation was investigated, which provided a target gene for improving fruit flavor and quality. [Methods] HpSWEET7 gene was isolated from ‘Zihonglong’, and sequence alignment and phylogenetic relationship were analyzed. Gene expression was analyzed by qRT-PCR, and the subcellular localization was detected by fusing fluorescent protein. Sugar transport activity was investigated by the yeast growth complementation and acidification assay. [Results] The ORF of HpSWEET7 was 771 bp, encoding 256 amino acid residues. HpSWEET7 contained two MtN3_saliva (Pfam No. PF03083) and seven transmembrane domains, which was closely related to Arabidopsis AtSWEET6 and AtSWEET7, belonging to SWEET Ⅱ class. Expression of HpSWEET7 in stems was lower than that in fruits at 6 developmental stages. The expression level was the highest in fruits at 20 d after pollination, gradually decreased with fruit development, and was the lowest in ripe fruits (30 d after pollination). Subcellular localization assay showed that HpSWEET7 was located at the cell membrane. HpSWEET7 showed transport activities for glucose, fructose, mannose, sorbitol and galactose. The acidification test further proved that Hp- SWEET7 transported glucose and fructose. [Conclusion] HpSWEET7 transports hexoses across the cell membrane, and participates in sugar accumulation during fruit development in red pitaya.